Palindromic rheumatism. II. Failure to detect circulating immune complexes during acute episodes. Issue 4 (August 1979) - Thompson, B; Mohammed, I; Holborow, E J; Currey, H L
Abstract : Thirty-eight samples of blood and 2 of synovial fluid were obtained from 19 patients suffering from palindromic rheumatism. In 12 cases samples were obtained from the same patient both during and between acute attacks. The presence of immune complexes was sought by a C1q-binding test. Most patients gave negative results: moderately elevated levels were obtained in a few. Broadly the pattern of results showed that individual patients were either positive or negative irrespective of whether they were in an attack or in remission. C3 and C4 measurements showed no significant abnormalities, confirming previous studies. Patients with elevated C1q-binding tests tended to be seropositive. We speculate that these are patients more likely to develop rheumatoid arthritis.